Physiological quality of sesame seeds produced from plants subjected to water stress - Silva, Ronimeire; Oliveira, Alexandre; Lopes, Maria de Fátima; Guimarães, Marcelo; Dutra, Alek (Revista Ciência Agronômica, 2016)
Germination and seed vigor may be influenced by several factors, such as water stress during production, which affect crops differently according to the phenological stage of the plant. The aim of this study therefore was to evaluate the physiological quality of sesame seeds from plants subjected to water stress at different phenological stages. To this end, sesame plants were subjected to water stress at the following stages: I - germination to the start of vegetative growth (T1); II - vegetative growth to flowering (T2); III - flowering to pod formation (T3); IV - fruit maturation (T4); also for stress at all stages (T5) and full irrigation (T6). By weighing and daily irrigation of the containers, levels were kept at 50% of pot capacity (CV) for treatments with water deficit, and at 100% CV for treatments with no deficit. At 90 days after planting, the plants were harvested. The seeds were evaluated by germination test, first germination count, germination speed index, mean germination time, accelerated aging, electrical conductivity, seedling emergence, emergence speed index, mean time of emergence, seedling length and seedling dry weight. Sesame seeds from plants grown under water deficit display lower physiological quality. Between germination and the start of vegetative growth, and between flowering and fruit formation, the sesame is more sensitive to water stress, so that water limitation during these periods results in the production of seeds of low physiological quality.